Preventing species extinctions: A global conservation consortium for Erica. Issue 4 (20th April 2022) - Pirie, Michael D.; Blackhall‐Miles, Robbie; Bourke, Greg; Crowley, Dan; Ebrahim, Ismail; Forest, Félix; Knaack, Michael; Koopman, Rupert; Lansdowne, Alex; Nürk, Nicolai M.; Osborne, Jo; Pearce, Timothy R.; et al.
Abstract : Societal Impact Statement: Human‐caused habitat destruction and transformation is resulting in a cascade of impacts to biological diversity, of which arguably the most fundamental is species extinctions. The Global Conservation Consortia (GCC) are a means to pool efforts and expertise across national boundaries and between disciplines in the attempt to prevent such losses in focal plant groups. GCC Erica coordinates an international response to extinction threats in one such group, the heaths, or heathers, of which hundreds of species are found only in South Africa's spectacularly diverse Cape Floristic Region. Summary: Effectively combating the biodiversity crisis requires coordinated conservation efforts. Botanic Gardens Conservation International (BGCI) and numerous partners have established Global Conservation Consortia (GCC) to collaboratively develop and implement comprehensive conservation strategies for priority threatened plant groups. Through these networks, institutions with specialised collections and staff can leverage ongoing work to optimise impact for threatened plant species. The genus Erica poses a challenge similar in scale to that of the largest other GCC group, Rhododendron, but almost 700 of the around 800 known species of Erica are concentrated in a single biodiversity hotspot, the Cape Floristic Region (CFR) of South Africa. Many species are known to be threatened, suffering the immediate impacts of habitat destruction, invasive species, changes in natural fire regimes and climate change. Efforts to counter these threats face general challenges: disproportionate burden of in situ conservation falling on a minority of the community, limited knowledge of species‐rich groups, shortfalls in assessing and monitoring threat, lack of resources for in situ and limitations of knowledge for ex situ conservation efforts and in communicating the value of biological diversity to a public who may never encounter it in the wild. GCC Erica brings together the world's Erica experts, conservationists and the botanical community, including botanic gardens, seed banks and organisations in Africa, Madagascar, Europe, the United States, Australia and beyond. We are collaboratively pooling our unique sets of skills and resources to address these challenges in working groups for conservation prioritisation, conservation in situ, horticulture, seed banking, systematic research and outreach. Abstract : Human‐caused habitat destruction and transformation is resulting in a cascade of impacts to biological diversity, of which arguably the most fundamental is species extinctions. The Global Conservation Consortia (GCC) are a means to pool efforts and expertise across national boundaries and between disciplines in the attempt to prevent such losses in focal plant groups. GCC Erica coordinates an international response to extinction threats in one such group, the heaths, or heathers, of which hundreds of species are found only in South Africa's spectacularly diverse Cape Floristic Region.